Catholic churches’ stances toward electoral manipulation in the post-Third Wave period - Osama Lotfy, Dina (Politics and religion, 2025)
As Catholic churches played a tremendous role in the third wave of democratization, it is crucial to examine their role in the current trends of autocratization. Given the potential for democratic backsliding resulting from elections, I study the official stances of national Catholic churches toward electoral manipulation in 59 cases across different regions, post-Third Wave. I find that 32% of the Catholic churches resisted electoral manipulation, while 34% called for peace, and 34% took no stance. I argue that beyond religious market dynamics, historical context also shapes Catholic churches’ cost-benefit calculations. Using logistic and multinomial regression models, I contend that Catholic churches resist electoral manipulation when government favoritism toward Catholicism is too low, even when they control a considerable proportion of the population. Additionally, the historical pro-democratizing role of Catholic churches positively influences their decision to resist electoral manipulation, particularly for those facing high competition in the religious market.